Integration of mass cytometry and single-cell RNA-sequencing of cells in bronchoalveolar lavage - Elizabeth Guinto; Sameeksha Chopra; I-Chih Kuo; Samuel B. Shin; Melina Messing; Chung Y. Cheung; Julia SW. Yang; Firoozeh V. Gerayeli; William Yip; Stephen Milne; Rachel L. Eddy; Janice M. Leung; et al. (BioTechniques, 2025)
Single-cell RNA sequencing (sc-RNA-seq) is a popular method for characterization of cell populations. However, the relationship between RNA and protein expression in cells is often discordant. Protein-based detection methods, such as cytometry by time-of-flight (CyTOF), can provide complementary data to sc-RNA-seq. We collected bronchoalveolar lavage (BAL) from healthy participants and co-evaluated cell populations and gene/protein expression by applying sc-RNA-seq and CyTOF to the same samples. Cell populations were well correlated between these two platforms, but differences emerged at the sub-population level. Notably, macrophage subtypes did not correlate well; whereas T-lymphocytes did. Gene and protein expression levels were significantly correlated (p < .01). Overall, we recommend CyTOF as a tool to validate sc-RNA-seq data for select proteins and cell populations in BAL samples.